2021
DOI: 10.1002/hpm.3363
|View full text |Cite
|
Sign up to set email alerts
|

Responsive policies needed to secure rural supply from increasing female doctors: A perspective

Abstract: Around the world, the supply of rural health services to address population health needs continues to be a wicked problem. Adding to this, an increasing proportion of female doctors is graduating from medical courses but gender is not accounted for within rural workforce policy and planning. This threatens the future capacity of rural medical services. This perspective draws together the latest evidence, to make the case for industry and government action on responsive policy and planning to attract females to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…This finding has been consistent with other cohorts and populations. However, it is of special concern in the medical field since the number of female physicians, and female medical students are increasing (O'Sullivan et al, 2022), and if the rates of suicide continue to increase, health services will suffer. Therefore, preventative methods are needed to target this population for the betterment of the health system in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…This finding has been consistent with other cohorts and populations. However, it is of special concern in the medical field since the number of female physicians, and female medical students are increasing (O'Sullivan et al, 2022), and if the rates of suicide continue to increase, health services will suffer. Therefore, preventative methods are needed to target this population for the betterment of the health system in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Female general surgeons typically work less hours and are less likely to reach leadership roles compared with males, possibly because they are fitting in other life commitments, such as caring roles. 7 General surgical training is long and typically occurs alongside major life milestones such as pregnancy and parenting, which may require time off work, particularly for maternity leave. Thirty-nine percent of our respondents took at least 6 months off during accredited training (commonly for parental leave).…”
Section: Discussionmentioning
confidence: 99%
“…Inflexible and longer hours may deter the recruitment and retention of female trainees into rural general surgical vacancies. 7 Supporting the non-professional needs of female rural general surgeons is also critical. Australian research has shown that female doctors move away from smaller rural centres when they have young children and a partner in the workforce, in contrast to their male colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations